Evaluating and understanding top of the atmosphere cloud radiative effects in Intergovernmental Panel on Climate Change (IPCC) Fifth Assessment Report (AR5) Coupled Model Intercomparison Project Phase 5 (CMIP5) models using satellite observations. Issue 2 (24th January 2013) - Wang, Hailan; Su, Wenying
Abstract : [1] In this study, the annual mean climatology of top of the atmosphere (TOA) shortwave and longwave cloud radiative effects in 12 Atmospheric Model Intercomparison Project (AMIP)‐type simulations participating in the Coupled Model Intercomparison Project Phase 5 (CMIP5) is evaluated and investigated using satellite‐based observations, with a focus on the tropics. Results show that the CMIP5 AMIPs simulate large‐scale regional mean TOA radiative fluxes and cloud radiative forcings (CRFs) well but produce considerably less cloud amount, particularly in the middle and lower troposphere. The good model simulations in tropical means, with multimodel mean biases of ‐3.6 W/m 2 for shortwave CRF and ‐1.0 W/m 2 for longwave CRF, are, however, a result of compensating errors over different dynamical regimes. Over the Maritime Continent, most of the models simulate moderately less high‐cloud fraction, leading to weaker shortwave cooling and longwave warming and a larger net cooling. Over subtropical strong subsidence regimes, most of the CMIP5 models strongly underestimate stratocumulus cloud amount and show considerably weaker local shortwave CRF. Over the transitional trade cumulus regimes, a notable feature is that while at varying amplitudes, most of the CMIP5 models consistently simulate a deeper and drier boundary layer, more moist free troposphere, and more high clouds and, consequently, overestimate shortwave cooling and longwave warming effects there. While most of the CMIP5 models show the same sign as the multimodel mean, there are substantial model spreads, particularly over the tropical deep convective and subtropical strong subsidence regimes. Representing clouds and their TOA radiative effects remains a challenge in the CMIP5 models. Abstract : Representing clouds radiative effects remains a challenge in the CMIP5 models